Single-crystal / polycrystal single-phase composite structure film with magnetoresistance response in wide temperature range and preparation method of single-crystal / polycrystal single-phase composite structure film
By introducing grain boundary and high-resistance polycrystalline phases into the manganese oxide film, a single crystal/polycrystalline single-phase composite structural film is formed, which solves the problem of magnetoresistance effect at low temperatures in the existing manganese oxide films, and realizes the magnetoresistance effect of the wide temperature zone and low magnetic field.
Patent Information
- Application Number
- CN202411664112.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-28
AI Technical Summary
The low-field magnetoresistance effect of existing manganese oxide films occurs much lower than room temperature, and their applications are limited near room temperature.
By introducing grain boundaries and high-resistance polycrystalline phases into the epitaxial single-crystalline manganese oxide film, a single-crystalline single-phase composite structure film is formed, and a single-crystalline/polycrystalline homogeneous composite structure LSMO thin film is deposited on a cracked LSMO single-crystalline film using pulsed laser deposition technology.
The temperature range of magnetoresistive response has been significantly broadened to 100-350K, achieving magnetoresistive effect under low magnetic field conditions under wide temperature zones, and is suitable for applications near room temperature.
Smart Images

Figure CN119530975A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thin film preparation, and in particular relates to a single crystal / polycrystalline single-phase composite structure thin film with wide temperature range magnetoresistance response and a preparation method thereof. Background Art
[0002] The colossal magnetoresistance (CMR) effect of typical magnetic semiconductor perovskite oxide manganese oxide has potential application prospects in spin electronics. However, the realization of its spin electronics application faces two practical problems: First, the significant magnetoresistance response temperature of single crystal manganese oxide is at its Curie point T. C The applicable temperature range is narrow and requires a large external magnetic field of several Tesla; secondly, the temperature range of the wide-temperature low-field magnetoresistance effect (LFMR) of polycrystalline perovskite manganese oxide is mostly at a low temperature of 10-150K, which cannot be used near room temperature.
[0003] At present, researchers have prepared self-assembled composite films by introducing non-magnetic insulating phases into manganese oxides, using the tunneling resistance of ferromagnetic / non-magnetic / ferromagnetic and the scattering effect of ferromagnetic / non-magnetic interfaces to improve the magnetoresistance of the composite films, and increasing the occurrence temperature of the low-field magnetoresistance effect by controlling the strain of the manganese oxide parent phase (Wang Kefeng, Liu Junming. Low-field magnetoresistance effect of rare earth manganese oxides [J]. Progress in Physics, 2003, 23(2): 20). However, this method is only applicable to a limited range of material systems, and the introduction of the second phase needs to consider many complex factors such as lattice matching, ion radius, barrier difference, size distribution, etc. (Adv. Funct. Mater. 2014, 24, 5393–5401). In addition, for the commonly used pulsed laser deposition method, it is necessary to select a suitable single crystal substrate, design a target material of multiple components and explore their deposition conditions separately, and the preparation process is complicated and expensive. Integrating oxide films with significant LFMR response in a wide temperature range on traditional semiconductor substrates has important practical value in the field of spintronic devices. Summary of the invention
[0004] In order to solve the problem in the prior art that the occurrence temperature of low-field magnetoresistance of manganese oxide films is far below room temperature, the purpose of the present invention is to provide a single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response and a preparation method thereof. The single crystal / polycrystalline single-phase composite structure LSMO film prepared by the method combines the room temperature magnetoresistance advantage of single crystal LSMO with the low temperature and low field magnetoresistance characteristics of polycrystalline LSMO, thereby increasing the occurrence temperature and realizing the wide temperature range low magnetic field magnetoresistance effect of manganese oxide films.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response, comprising the following steps:
[0007] LSMO single crystal thin films with cracks were prepared on target substrates by using water-soluble sacrificial layer technology;
[0008] A single crystal / polycrystalline homogeneous composite LSMO film is deposited on a cracked LSMO single crystal film by pulsed laser deposition technology to form a single crystal / polycrystalline single-phase composite structure film with a wide temperature range magnetoresistance response.
[0009] Furthermore, the thickness of the LSMO film of the single crystal / polycrystalline homogeneous composite structure is 200-500 nm.
[0010] Furthermore, the water-soluble material is Sr3Al2O6.
[0011] Furthermore, the target substrate material is Si wafer, quartz, mica or Al2O3.
[0012] Furthermore, a LSMO single crystal film with cracks is prepared on a target substrate by a water-soluble sacrificial layer technology, comprising the following steps:
[0013] Epitaxial SAO sacrificial layer was grown on STO substrate by pulsed laser deposition technology;
[0014] Epitaxial LSMO layer was grown on the SAO sacrificial layer by pulsed laser deposition technology;
[0015] A support layer is attached on the top of the LSMO layer, and a SAO sacrificial layer is dissolved on the STO substrate to release the LSMO layer, thereby forming a LSMO single crystal film with cracks, and the LSMO single crystal film with cracks is transferred to a target substrate.
[0016] Furthermore, the SAO sacrificial layer is a cubic phase, and the SAO lattice constant of the cubic phase is
[0017] The STO substrate has a cubic structure and the lattice constant is
[0018] The lattice constant of LSMO is The lattice constants of the LSMO layer and the SAO layer are in a multiple relationship.
[0019] Furthermore, the STO substrate includes an STO single crystal with crystal plane orientations in (001), (110) and (111) directions.
[0020] Furthermore, the support layer material is a thermal release tape, polydimethylsiloxane, polypropylene carbonate, polymethyl methacrylate or hard photoresist.
[0021] Furthermore, the thickness of the SAO sacrificial layer is 30-50 nm, and the thickness of the LSMO layer is 5-10 nm.
[0022] A single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response, wherein the magnetoresistance response temperature range of the single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response is 100-350K.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] In the present invention, the high Curie temperature of the single crystal phase is combined with the spin-polarized tunneling (SPT) and / or spin-dependent scattering (SDS) of the conduction electrons at the grain boundary of the polycrystalline phase by artificially introducing the grain boundary and the high-resistance polycrystalline phase in the epitaxial single crystal manganese oxide film. In the present invention, the single-phase structure manganese oxide film does not need to consider the reaction problem between the second phase doping material and the raw material. The controllable polycrystalline LSMO film design boundary structure is artificially introduced into the single crystal LSMO film, and the local spin disorder existing on the polycrystalline grain boundary can lead to a larger LFMR effect at low temperature. Due to the difference in the ferromagnetic-paramagnetic transition temperature of the single crystal LSMO and polycrystalline LSMO films, the temperature range of the ferromagnetic-paramagnetic transition will be significantly broadened, thereby expanding the magnetoresistance response temperature range of the single crystal / polycrystalline single-phase composite structure film to 100-350K. The single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response prepared by the present invention can be grown on any high temperature resistant non-lattice matching substrate, thereby expanding the composition range that can form such a microstructure, which provides the potential for building a layered nanostructure on an integrated technology Si substrate or a flexible Mica substrate. In addition, the magnetic domain arrangement of single crystal / polycrystalline composite materials on different substrates is diverse, and the sensitivity to the direction of the applied magnetic field is different. The magnetic domain can be regulated by cleverly designing the lattice mismatch between the substrate and the film, opening up more opportunities for application in magnetic sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A schematic diagram of the process of preparing and transferring the LSMO / SAO heterostructure and epitaxially growing a single crystal / polycrystalline single-phase LSMO thin film on a target substrate provided by the present invention;
[0026] Figure 2 Schematic diagram of releasing a LSMO film with a crack structure on a target substrate after dissolving the SAO buffer layer, wherein (a) is a schematic diagram of the regular crack structure generated by the rupture of the LSMO film after peeling, and (b) is a schematic diagram of two types of nucleation sites obtained by transferring the LSMO film with a crack structure to the target substrate;
[0027] Figure 3 The structure of the single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response prepared by the present invention;
[0028] Figure 4 Optical photograph of the transferred LSMO film with regular crack structure;
[0029] Figure 5 The resistance-temperature curves of LSMO thin films, where (a) is the resistance-temperature (RT) curve of LSMO single crystal thin film epitaxially grown on STO (001) substrate; (b) is the RT curve of LSMO polycrystalline thin film grown on Mica (001) substrate;
[0030] Figure 6 Are magnetoresistance curves, where (a) is the magnetoresistance curve of the LSMO single crystal film grown on the STO (001) substrate at room temperature 300K; (b) is the magnetoresistance curve of the LSMO polycrystalline film grown on the Mica (001) substrate at 115K. DETAILED DESCRIPTION
[0031] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0032] Single crystal / polycrystalline single-phase composites are different from previously reported self-assembled oxide nanocomposites. The former grows polycrystalline and coherent epitaxial single crystal thin films on independent templates provided by non-lattice matching target substrates and ultra-thin independent LSMO epitaxial films, respectively, and the single-phase structure is simple and controllable, while the latter is composed of two or more different materials, and many factors need to be considered, such as the lattice matching degree of the two phases, composition changes, interface potential barrier difference, and second phase size and distribution.
[0033] The present invention provides a new strategy to prepare a single-crystal / polycrystalline single-phase composite structure film, aiming to achieve a controllable single-phase manganese oxide composite film with a simple structure and a wide temperature range magnetoresistance response. The prepared single-phase manganese oxide composite film can be flexibly constructed on other substrates to be better suitable for practical application environments.
[0034] The present invention uses a pulsed laser deposition method to sequentially deposit a strontium aluminate Sr3Al3O6 (SAO) sacrificial layer and an epitaxial manganese oxide La on a strontium titanate SrTiO3 (STO) single crystal substrate. 0.7 Sr 0.3MnO3 (LSMO) film, STO substrate, SAO sacrificial layer and LSMO film are arranged in sequence from bottom to top to form a high-quality orderly arranged LSMO / SAO heterostructure; the water solubility of SAO is used to separate the epitaxial LSMO film from the STO substrate by peeling technology, and the LSMO film is broken by the complete release of lattice strain and the liquid flow during the water erosion process when the LSMO film is peeled off, and the LSMO film is transferred to the target substrate to obtain a LSMO single crystal film with regular cracks. Thus, two different nucleation sites, the LSMO single crystal film and the non-lattice matching substrate exposed at the crack, are introduced on the target substrate, and high-temperature pulsed laser deposition is performed on this substrate to form a single crystal / polycrystalline single-phase composite LSMO film, that is, a single crystal / polycrystalline single-phase composite film with wide temperature range magnetoresistance response is obtained.
[0035] Specifically, the method for preparing a single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response of the present invention is to prepare a LSMO single crystal film with cracks on a target substrate by using a water-soluble sacrificial layer technology with a water-soluble material;
[0036] A single crystal / polycrystalline homogeneous composite LSMO film is deposited on a cracked LSMO single crystal film by pulsed laser deposition technology to form a single crystal / polycrystalline single-phase composite film with wide temperature range magnetoresistance response. Specifically, the following steps are included:
[0037] Step 1, pretreatment of the STO substrate: including ultrasonic cleaning, acid etching and annealing to obtain a smooth and well-stepped surface morphology;
[0038] Step 2, epitaxially growing a SAO sacrificial layer on the STO substrate by pulsed laser deposition technology;
[0039] Step 3, epitaxially growing a LSMO layer on the SAO sacrificial layer by pulsed laser deposition technology;
[0040] Step 4, attaching a support layer on the top of the LSMO layer, dissolving the SAO sacrificial layer from the STO substrate to release the LSMO layer, forming a LSMO single crystal film with cracks, and transferring the LSMO single crystal film with cracks to a target substrate; the LSMO single crystal film with cracks transferred to the target substrate and the target substrate exposed at the cracks can be used as nucleation sites for LSMO single crystals and polycrystalline, respectively; the target substrate material is any one of Si wafers, quartz, mica or Al2O3, which is resistant to high temperatures and does not match the LSMO lattice, so as to facilitate the subsequent high-temperature deposition and growth of LSMO films with a single crystal / polycrystalline homogeneous composite structure;
[0041] Step 5, depositing an LSMO film on the LSMO single crystal film with cracks by pulsed laser deposition technology to obtain a single crystal / polycrystalline homogeneous composite structure LSMO film; wherein the thickness of the single crystal / polycrystalline homogeneous composite structure LSMO film is 200-500nm. Wherein, the water-soluble material includes Sr3Al2O6 and its doped (Ca, Sr, Ba)3Al2O6 series. By adjusting the ratio of the three elements Ca, Sr, and Ba, the lattice constant of the sacrificial layer can be adjusted from 0.382nm (Ca3Al2O6) to 0.413nm (Ba3Al2O6) to adjust the lattice stress of the epitaxial LSMO and the crack width and density of the LSMO single crystal film after transfer;
[0042] Step 6: Deposit a metal electrode layer on the single crystal / polycrystalline homogeneous composite LSMO film by magnetron sputtering technology for physical transport performance testing. Use a physical property measurement system (PPMS) to measure the transport performance in the range of 100K to 400K, and the test magnetic field is parallel to the sample surface.
[0043] The thickness of the metal electrode layer is 50 nm, and the metal is Pt or Au. In the present invention, the SAO sacrificial layer is a cubic phase, and the SAO lattice constant of the cubic phase is The STO substrate has a cubic structure and the lattice constant is The lattice constants of the LSMO layer and the SAO layer are in a multiple relationship, so they can be grown epitaxially.
[0044] In the present invention, the STO substrate includes three STO single crystals with crystal plane orientations of (001), (110) and (111). The stress and nanostructure morphology of the grown LSMO film can be effectively regulated by changing the orientation of the STO substrate and other conditions.
[0045] In the present invention, the SAO sacrificial layer can be completely dissolved by deionized water at room temperature, thereby completely releasing the upper LSMO film.
[0046] In the present invention, the LSMO / SAO has a vertically aligned interface. Due to the lattice mismatch between LSMO and SAO, And compressive strain is generated between LSMO nanocrystals.
[0047] In the present invention, during the water erosion of the SAO sacrificial layer, the stress in the lattice of the LSMO epitaxial single crystal structure is released, and it is very easy to break under the impact force of the liquid flow. During the process of heating and transferring to the target substrate, its fragile ultra-thin film structure is further broken by the external stress, forming an LSMO single crystal film with regular cracks on the target substrate.
[0048] In the present invention, the support layer material is a thermal release tape (Revalpha 319Y-4M), polydimethylsiloxane (PDMS), polypropylene carbonate (PPC), polymethyl methacrylate (PMMA) or hard photoresist. Support layers with different viscosities and hardnesses will result in different crack densities.
[0049] In the present invention, the target substrate material includes any one of Si wafer, quartz, mica or Al2O3, which is resistant to high temperature and does not match the LSMO lattice, so as to facilitate the subsequent high temperature deposition and growth of single crystal / polycrystalline composite LSMO thin film;
[0050] In the present invention, the residue on the STO substrate can be removed by a buffered etching solution (BOE, HF: NH4F mass ratio is 1:6), thereby promoting the reusability of the substrate and reducing the production cost.
[0051] The single-phase structured manganese oxide film in the present invention does not need to consider the reaction problem between the second phase doping material and the raw material. The controllable polycrystalline LSMO film design boundary structure is artificially introduced into the single crystal LSMO film, and the local spin disorder existing on the polycrystalline grain boundary can lead to a larger LFMR effect at low temperature. Due to the difference in ferromagnetic-paramagnetic transition temperature between single crystal LSMO and polycrystalline LSMO films, the temperature range of their ferromagnetic-paramagnetic transition will be significantly broadened, thereby expanding the response temperature range of the single crystal / polycrystalline single-phase composite structure film magnetoresistance with wide temperature range magnetoresistance response to 100-350K.
[0052] Example 1
[0053] See also Figures 1 to 3 A single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response includes an STO substrate, a SAO sacrificial layer and a LSMO film; the STO substrate, the SAO sacrificial layer and the LSMO film are arranged in sequence from bottom to top.
[0054] like Figure 1 As shown, the present invention provides a method for preparing the single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response, comprising the following steps:
[0055] Pretreatment of STO single crystal substrate: ultrasonic cleaning with acetone, ethanol and deionized water for 10 minutes respectively to remove organic matter, metal ions and impurity particles on the substrate surface, and immerse the surface of STO (001) substrate in buffered hydrofluoric acid for 20 seconds and anneal in a furnace at 1100 ° C for 6 hours to obtain a smooth and well-stepped surface morphology, which is convenient for the subsequent adsorption and growth of thin films;
[0056] With Sr3Al2O6 as the target, the first layer was deposited on the clean STO substrate by pulsed laser deposition to form a SAO sacrificial layer. The growth temperature was 800℃, the oxygen atmosphere was preferably 20Pa, the deposition rate was 3Hz, and the laser energy density was 2J / cm 2 , the target-substrate distance is 6 cm, the deposition time is 10 min, and the thickness of the SAO sacrificial layer is 30-50 nm;
[0057] Based on component La 0.7 Sr 0.3 The LSMO ultra-thin film was grown on a clean STO substrate using a pulsed laser deposition method using a MnO3 polycrystalline target. The growth temperature was 700°C, the oxygen atmosphere was preferably 30Pa, the deposition rate was 10Hz, and the laser energy density was 1.2J / cm 2 , the target-substrate distance is 6 cm, and the thickness of the LSMO ultra-thin film is 5-10 nm;
[0058] A thermal exfoliation tape (Revalpha 319Y-4M) is covered on the upper surface of the grown LSMO ultra-thin film as a support layer, and then immersed in deionized water, so that the SAO sacrificial layer is completely dissolved by the deionized water at room temperature, thereby exfoliating the flexible LSMO film to obtain a thermal exfoliation tape / LSMO structure;
[0059] The thermal release tape / LSMO structure was transferred onto a Mica (001) substrate by releasing the thermal release tape by heating on a hot plate at a temperature of 120° C. to obtain a LSMO / Mica substrate.
[0060] Take La 0.7 Sr 0.3 MnO3 was used as the target material, and pulsed laser deposition was used to deposit the second single crystal / polycrystalline composite LSMO thin film on the surface of the LSMO / Mica substrate. The growth temperature was 700°C, the oxygen atmosphere was preferably 30Pa, the deposition rate was 10Hz, and the laser energy density was 1.2J / cm 2 , the target-substrate distance is 6 cm, and the LSMO film thickness is 200 nm;
[0061] A metal electrode layer is deposited on a single crystal / polycrystalline homogeneous composite structure LSMO film by magnetron sputtering technology to obtain a single crystal / polycrystalline single-phase composite structure film with a wide temperature range magnetoresistance response for physical transport performance testing.
[0062] In the present invention, the release of lattice internal stress and the external stress during the film peeling transfer process generate cracks in the LSMO film. The localized intact LSMO single crystals between the cracks serve as nucleation sites for the second LSMO single crystal film growth. Due to the lattice mismatch at the cracks, a LSMO polycrystalline film is deposited on the exposed target substrate, such as Figure 2As shown in (a) and (b), it can be seen that the non-lattice-matched target substrate and the ultra-thin independent LSMO epitaxial film provide independent templates for polycrystalline growth and coherent epitaxial growth, respectively.
[0063] See also Figure 3 The target substrate prepared in the present invention has a single crystal / polycrystalline LSMO layered structure, and a polycrystalline LSMO layer is distributed in the single crystal LSMO layer.
[0064] See also Figure 4 , it can be seen that the transferred LSMO film has a crack structure, the crack distribution is relatively regular, and the crack width and density can be regulated according to the lattice stress between the LSMO film and the sacrificial layer.
[0065] Figure 4 (a) shows the resistance-temperature (RT) curve of the LSMO single crystal film epitaxially grown on the STO (001) substrate. The metal-insulator transition temperature of the single crystal LSMO film is about 370K. Figure 4 (b) shows the RT curve of LSMO polycrystalline film grown on Mica (00l) substrate. The metal-insulator transition temperature of polycrystalline LSMO film is about 250 K. It can be expected that the layered microstructure of single crystal / polycrystalline composite LSMO film will significantly broaden the temperature range of its ferromagnetic-paramagnetic transition and further expand the response temperature range of macroscopic magnetoresistance under the double exchange mechanism.
[0066] Figure 5 (a) shows the magnetoresistance curve of LSMO single crystal film epitaxially grown on STO (001) substrate at room temperature 300K. The magnetoresistance reaches nearly 8% under 5000Oe magnetic field. Figure 5 (b) shows the magnetoresistance curve of LSMO polycrystalline film grown on Mica (001) substrate at 115K, and the magnetoresistance is about 10% under 5000Oe magnetic field. The layered microstructure of single crystal / polycrystalline composite LSMO film can satisfy its significant magnetoresistance response in a wide temperature range below Curie temperature (about 370K).
[0067] Example 2
[0068] Pretreatment of STO single crystal substrate: ultrasonic cleaning with acetone, ethanol and deionized water for 10 minutes respectively to remove organic matter, metal ions and impurity particles on the substrate surface, and immerse the STO substrate surface in buffered hydrofluoric acid for 20 seconds, and anneal in a furnace at 1100°C for 6 hours to obtain a smooth and well-stepped surface morphology, which is convenient for the subsequent adsorption and growth of thin films;
[0069] With Sr3Al2O6 as the target, the first layer was deposited on a clean STO (110) substrate by pulsed laser deposition to form a SAO sacrificial layer. The growth temperature was 800 °C, the oxygen atmosphere was preferably 20 Pa, the deposition rate was 3 Hz, and the laser energy density was 2 J / cm 2 , the target-substrate distance is 6 cm, the deposition time is 15 min, and the thickness of the SAO sacrificial layer is 30-50 nm;
[0070] Based on component La 0.7 Sr 0.3 The LSMO ultra-thin film was grown on a clean STO substrate using a pulsed laser deposition method using a MnO3 polycrystalline target at a growth temperature of 700°C, an oxygen atmosphere of 30 Pa, a deposition rate of 10 Hz, and a laser energy density of 1.2 J / cm 2 , the target-substrate distance is 6 cm, and the thickness of the LSMO ultra-thin film is 5-10 nm;
[0071] The surface of the grown LSMO ultra-thin film is covered with polydimethylsiloxane (PDMS) as a supporting layer, and then immersed in deionized water, so that the SAO sacrificial layer is completely dissolved by the deionized water at room temperature, so that the LSMO film is successfully separated from the substrate and electrostatically adsorbed onto the PDMS, obtaining a PDMS / LSMO structure;
[0072] The PDMS / LSMO structure was pressed onto the Si wafer substrate so that the bottom surface of the LSMO film was in close contact with the Si wafer. The entire sample (including the Si wafer, LSMO film and PDMS support layer) was then heated at 80°C for 15 minutes. After heating, the PDMS support layer was separated, allowing the LSMO film layer with cracks to successfully adhere to the silicon wafer, thus obtaining the LSMO / Si substrate.
[0073] Take La 0.7 Sr 0.3 MnO3 was used as the target material, and a second single crystal / polycrystalline composite LSMO thin film was deposited on the surface of the LSMO / Si substrate by pulsed laser deposition to obtain a single crystal / polycrystalline single-phase composite thin film with wide temperature range magnetoresistance response. The deposition growth temperature was 700°C, the oxygen atmosphere was 30Pa, the deposition rate was 10Hz, and the laser energy density was 1.2J / cm 2 , the target-substrate distance is 6 cm, and the LSMO film thickness is 300 nm.
[0074] Example 3
[0075] Pretreatment of STO single crystal substrate: ultrasonic cleaning with acetone, ethanol and deionized water for 10 minutes respectively to remove organic matter, metal ions and impurity particles on the substrate surface, and immerse the surface of STO (111) substrate in buffered hydrofluoric acid for 20 seconds and anneal in a furnace at 1100 ° C for 6 hours to obtain a smooth and well-stepped surface morphology, which is convenient for the subsequent adsorption and growth of thin films;
[0076] With Sr3Al2O6 as the target, the first layer was deposited on the clean STO substrate by pulsed laser deposition to form a SAO sacrificial layer. The growth temperature of the deposition was 800°C, the oxygen atmosphere was preferably 20Pa, the deposition rate was 3Hz, and the laser energy density was 2J / cm 2 , the target-substrate distance is 6 cm, the deposition time is 15 min, and the thickness of the SAO sacrificial layer is 30-50 nm;
[0077] Based on component La 0.7 Sr 0.3 The LSMO ultra-thin film was grown on a clean STO substrate using a pulsed laser deposition method using a MnO3 polycrystalline target at a growth temperature of 700°C, an oxygen atmosphere of 30 Pa, a deposition rate of 10 Hz, and a laser energy density of 1.2 J / cm 2 , the target-substrate distance is 6 cm, and the thickness of the LSMO ultra-thin film is 5-10 nm;
[0078] Spin-coat a photoresist on the surface of the grown LSMO ultra-thin film and solidify it as a support layer, then soak it in deionized water so that the SAO sacrificial layer is completely dissolved by the deionized water at room temperature, thereby peeling off the flexible LSMO film to obtain a photoresist / LSMO structure;
[0079] The photoresist / LSMO structure is transferred onto a quartz substrate, with the LSMO layer closely attached to the substrate surface. The photoresist layer is removed by gently dropping acetone on the upper photoresist layer, and then slowly rinsed with deionized water for multiple times to obtain the LSMO / quartz substrate.
[0080] Take La 0.7 Sr 0.3 MnO3 was used as the target material, and pulsed laser deposition was used to deposit a second single crystal / polycrystalline composite LSMO thin film on the surface of the LSMO / quartz substrate to obtain a single crystal / polycrystalline single-phase composite thin film with wide temperature range magnetoresistance response. The deposition growth temperature was 700°C, the oxygen atmosphere was 30Pa, the deposition rate was 10Hz, and the laser energy density was 1.2J / cm 2 , the target-substrate distance is 6 cm, and the LSMO film thickness is 400 nm.
[0081] The target substrate material in the present invention may also be Al2O3. The support layer material may also be polymethyl methacrylate or polypropylene carbonate.
[0082] The above description is only for the best embodiment of the present invention, but it should not be understood as limiting the claims. The present invention is not limited to the above embodiments, and its specific structure is allowed to be changed. However, all changes made within the protection scope of the independent claims of the present invention are within the protection scope of the present invention.
[0083] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
Claims
1. A method for preparing a single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response, characterized in that: The following steps are involved: LSMO single crystal thin films with cracks were prepared on target substrates by using water-soluble sacrificial layer technology; A single crystal / polycrystalline homogeneous composite LSMO film is deposited on a cracked LSMO single crystal film by pulsed laser deposition technology to form a single crystal / polycrystalline single-phase composite structure film with a wide temperature range magnetoresistance response.
2. The method for preparing a single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response according to claim 1, characterized in that: The thickness of the LSMO film of the single crystal / polycrystalline homogeneous composite structure is 200-500nm.
3. The method for preparing a single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response according to claim 1, characterized in that: The water-soluble material is Sr3Al2O6.
4. The method for preparing a single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response according to claim 1, characterized in that: The target substrate material is Si wafer, quartz, mica or Al2O3.
5. The method for preparing a single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response according to claim 1, characterized in that: A LSMO single crystal film with cracks is prepared on a target substrate by a water-soluble sacrificial layer technology, comprising the following steps: Epitaxial SAO sacrificial layer was grown on STO substrate by pulsed laser deposition technology; Epitaxial LSMO layer was grown on the SAO sacrificial layer by pulsed laser deposition technology; A support layer is attached on the top of the LSMO layer, and a SAO sacrificial layer is dissolved on the STO substrate to release the LSMO layer, thereby forming a LSMO single crystal film with cracks, and the LSMO single crystal film with cracks is transferred to a target substrate.
6. The method for preparing a single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response according to claim 5, characterized in that: The SAO sacrificial layer is a cubic phase, and the SAO lattice constant of the cubic phase is The STO substrate has a cubic structure and the lattice constant is The lattice constant of LSMO is The lattice constants of the LSMO layer and the SAO layer are in a multiple relationship.
7. The method for preparing a single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response according to claim 5, characterized in that: The STO substrate includes an STO single crystal with crystal plane orientations in (001), (110) and (111) directions.
8. The method for preparing a single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response according to claim 5, characterized in that: The support layer material is a thermal release tape, polydimethylsiloxane, polypropylene carbonate, polymethyl methacrylate or hard photoresist.
9. The method for preparing a single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response according to claim 5, characterized in that: The thickness of the SAO sacrificial layer is 30-50 nm, and the thickness of the LSMO layer is 5-10 nm.
10. A single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response prepared by the method according to any one of claims 1 to 9, characterized in that: The magnetoresistance response temperature range of the single crystal / polycrystalline single-phase composite structure film with wide temperature range magnetoresistance response is 100-350K.